Innovations in production technology of jet fuel - Єфименко, В.В.; Мороз, Т.Т.; Єфіменко, С.В. (Proceedings of National Aviation University, 2008)
The technological processes of jet fuel ТС-1 production and possibility of additional refinement and stabilization methods introduction by means of bentonite clays at the Kremenchug Refinery are considered.